Science and Technology in Homeric Epics - Paipetis, S. A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
In the Homeric Epics, important references to specific autonomous systems and mechanisms of very advanced technology, such as automata and artificial intelligence, as well as to almost modern methods of design and production are included. Even if those features of Homeric science were just poetic concepts (which on many occasions does not explain the astonishing details of design and manufacture, like the ones included in the present volume), they seem to prove that these achievements were well within human capability. In addition, the substantial development of machine theory during the early post-Homeric age shows that the Homeric descriptions were a kind of prophetic conception of these machines, and scientific research must be a quest for the fundamental principles of knowledge available during the Late Bronze Age and the dawn of the Iron Age. Such investigations must of necessity be strongly interdisciplinary and also proceed continuously in time, since, as science progresses, new elements of knowledge are discovered in the Homeric Epics, amenable to scientific analysis. This book brings together papers presented at the international symposium Science and Technology in Homeric Epics, which took place at Ancient Olympia in 2006. It includes a total of 41 contributions, mostly original research papers, covering diverse fields of science and technology, in the modern sense of these words.
General Themes -- Mycenaean Technology -- Autagreton -- Mathematics and Physics -- Archimedes' Count of Homer's Cattle of the Sun -- Vortices in Homer's Odyssey — A Scientific Approach -- The Homeric Automata and Their Implementation -- The River Ocean: Homer's Cosmogony -- The Laws of Curvilinear Motion in the Iliad -- Materials -- Iron in the Homeric Epics & Homer, a Sensible Ecologist -- Early Bronze Technology at Land's End, North Western Iberia -- Porphyra: In Search of Dyeing Methods in Ancient Greece -- Technology Transfer in the Bronze Age: The Case of a Faience-Like Blue Glaze Produced at Bread-Oven Temperatures -- DefensiveWeapons -- From Homer to Hoplite: Scientific Investigations of Greek Copper Alloy Helmets -- Defensive Weapons in Homer -- How the Greeks Got Ahead: Technological Aspects of Manufacture of a Corinthian Type Hoplite Bronze Helmet from Olympia -- Telecommunications -- Theoretical Analysis of Telecommunication through “Friktories” -- Geology — Geomechanics -- Elements of Engineering Geology and Geotechnical Engineering in the Homeric Poems -- Geological Knowledge of Greeks in the Era of Trojan War -- Static and Dynamic Analysis of the Atreus Vaulted Tomb in Mycenae -- Medicine -- Homeric Injury Scenes on Ancient Greek Pottery Reveal Medical Knowledge -- The Healing Art in the Iliad -- Medicinal Herbs and Plants in Homer -- Flora and Fauna -- Agricultural Development in the Homeric Era -- The Fauna of Greece and Adjacent Areas in the Age of Homer -- Astronomy -- “Eneoros Minos” and the Minoan Calendrical Abacus -- The Divine Fires of Creation: Homeric Hephaestos as a Comet/Meteor God -- A Comet during the Trojan War? -- Homeric Calendar and Helios Charioteer -- Homer and Orosius: A Key to Explain Deucalion's Flood, Exodus and Other Tales -- Seafaring -- Homer at Sea (????????? ???????) -- The Redness of Ulysses' Ships -- Cultural Environment -- Ambrosia, Nectar and Elaion in the Homeric Poems -- Dietary Habits in Homer -- Geography -- Trojan Plain and Homeric Topography -- General Interest -- Mêtis and the Artificial -- Interpreting the Representations on the Shield of Achilles -- Homer and the So-Called Homeric Questions -- Atlantis in Homer and Other Authors Prior to Plato -- Did Ulysses Travel to Atlantis? -- Homer's Reference to Writing in Proitos' Era -- Linguistic Science and Script Technology: The Homeric Evidence -- The Miraculous Homeric Metre.
Keywords: Engineering design; History; Engineering Design; History of Science; History, general